ANALISIS PENAFSIRAN TERHADAP Q.S AL-MA’IDAH: 38 DALAM QUR’AN: A REFORMIST TRANSLATION: (A Reformist Translation)
Edip Yuksel and his colleages considered Qur’an: A Reformist Translation as a progressive work which is different from previous translation in English. One of the verses of the Qur’an that is often misunderstood is QS. al-Ma’idah (5): 38. The verse talks about the punishment for a burglar. All of translator interpret fakt